Oligomerization and Spatial Distribution of Kvβ1.1 and Kvβ2.1 Regulatory Subunits - Roig, Sara R.; Cassinelli, Silvia; Zeug, Andre; Ponimaskin, Evgeni; Felipe, Antonio (Frontiers in Physiology, 2022)
Members of the regulatory Kvβ family modulate the kinetics and traffic of voltage-dependent K+ (Kv) channels. The crystal structure of Kv channels associated with Kvβ peptides suggests a 4/4 composition. Although Kvβ2 and Kvβ1 form heteromers, evidence supports that only Kvβ2.1 forms tetramers in the absence of  subunits. Therefore, the stoichiometry of the Kvβ oligomers fine-tunes the activity of hetero-oligomeric Kv channel complexes. We demonstrate that Kvβ subtypes form homo- and heterotetramers with similar affinities. The Kvβ1.1/Kvβ2.1 heteromer showed an altered spatial distribution in lipid rafts, recapitulating the Kvβ1.1 pattern. Because Kvβ2 is an active partner of the Kv1.3-TCR complex at the immunological synapse (IS), an association with Kvβ1 would alter this location, shaping the immune response. Differential regulation of Kvβs influences the traffic and architecture of the Kvβ heterotetramer, modulating Kvβ-dependent physiological responses.